Effect of ageing treatment on microstructures, mechanical properties and corrosion behavior of Mg-Zn-RE-Zr alloy micro-alloyed with Ca and Sr - *Yu Fu; Chen Liu; Hai Hao (China Foundry, 2021)
Effects of ageing treatment on the microstructures, mechanical properties and corrosion behavior of the Mg-4.2Zn-1.7RE-0.8Zr-xCa-ySr [x=0, 0.2 (wt.%), y=0, 0.1, 0.2, 0.4 (wt.%)] alloys were investigated. Results showed that Ca or/and Sr additions promoted the precipitation hardening behavior of Mg-4.2Zn-1.7RE-0.8Zr alloy and shortened the time to reaching peak hardness from 13 h to 12 h. The maximum hardness of 77.1±0.6 HV for the peak-aged Mg-4.2Zn 1.7RE-0.8Zr-0.2Ca-0.2Sr alloy was obtained. The microstructures of peak-aged alloys mainly consist of α-Mg phase, Mg51Zn20 phase and ternary T-phase. The Zn-Zr phase is formed within the α-Mg matrix, and the Mg2Ca phase is formed near T-phase due to the enrichment of Ca in front of the solid-liquid interface. Furthermore, fine short rod-shaped β′1 phase is precipitated within the α-Mg matrix in the peak-aged condition. The peak-aged Mg-4.2Zn-1.7RE-0.8Zr-0.2Ca 0.2Sr alloy exhibits optimal mechanical properties with an ultimate tensile strength of 208 MPa, yield strength of 150 MPa and elongation of 3.5%, which is mainly attributed to precipitation strengthening. In addition, corrosion properties of experimental alloys in the 3.5wt.% NaCl solution were studied by the electrochemical tests, weight loss, hydrogen evolution measurement and corrosion morphology observation. The results suggest that peak-aged alloys show reduced corrosion rates compared with the as-cast alloys, and minor additions of Ca and/or Sr improve the corrosion resistance of the Mg-4.2Zn-1.7RE-0.8Zr alloy. The peak-aged Mg-4.2Zn-1.7RE-0.8Zr-0.2Ca-0.2Sr alloy possesses the best corrosion resistance, which is mainly due to the continuous and compact barrier wall constructed by the homogeneous and continuous second phases.